Human resource management: Cocepts, theories and contemporary practices - Sharma, R. C.; Sharma, Nipun (London Routledge, 2025)
This textbook introduces readers to an array of concepts and current practices of human resource management (HRM). It provides an understanding of the current problems in the area that require pragmatic research and realistic solutions. Using a blend of diverse concepts theories tools and techniques the book discusses contemporary practices of HRM and the challenges related to acquiring and training people human resource development compensation and reward employee relations technological changes HR records audit research and more.